The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1088/1741-2552/ac1176
|View full text |Cite
|
Sign up to set email alerts
|

Myoelectric control of robotic lower limb prostheses: a review of electromyography interfaces, control paradigms, challenges and future directions

Abstract: Objective. Advanced robotic lower limb prostheses are mainly controlled autonomously. Although the existing control can assist cyclic movements during locomotion of amputee users, the function of these modern devices is still limited due to the lack of neuromuscular control (i.e. control based on human efferent neural signals from the central nervous system to peripheral muscles for movement production). Neuromuscular control signals can be recorded from muscles, called electromyographic (EMG) or myoelectric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 145 publications
1
58
0
Order By: Relevance
“…Limited research has investigated the utilization of bilateral modalities which contain meaningful interlimb coordination information, such as the gait phase delay across the legs, not to mention fusing the contralateral neural information to additionally extract the motion intention. The decoding accuracy exhibits no difference when we replaced the ipsilateral sEMG with the contralateral sEMG ( Figure 3B ) with a p -value indicator of 0.98, this supports the complementary myocontrol rationale with respect to myocontrol from the residual limb (Fleming et al, 2021 ). Moreover, as indicated in Hu's research (Hu et al, 2018 ), bilateral sensors fusion can reduce steady-state and transitional error rates in locomotion recognition.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Limited research has investigated the utilization of bilateral modalities which contain meaningful interlimb coordination information, such as the gait phase delay across the legs, not to mention fusing the contralateral neural information to additionally extract the motion intention. The decoding accuracy exhibits no difference when we replaced the ipsilateral sEMG with the contralateral sEMG ( Figure 3B ) with a p -value indicator of 0.98, this supports the complementary myocontrol rationale with respect to myocontrol from the residual limb (Fleming et al, 2021 ). Moreover, as indicated in Hu's research (Hu et al, 2018 ), bilateral sensors fusion can reduce steady-state and transitional error rates in locomotion recognition.…”
Section: Discussionsupporting
confidence: 73%
“…Their design can guarantee an immediate response when the gait speeds change and meet the basic daily demands of the amputee. Besides, if motion intention is decoded from the healthy leg of the amputee, it may provide a better choice to overcome the shortcomings of the poor signal quality when the sEMG was captured from the residual limb (Fleming et al, 2021 ). Moreover, the sEMG is especially suitable for monitoring muscle activity patterns during walking, this can provide an additional benefit in the gait restoration assessment at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…CPR5 associated with a novel nucleoporin PLANT NUCLEAR ENVELOPE TRANSMEMBRANE 1 (PNET1) [ 40 ]. Function of human PNET1 homologs is important to cell cycle regulation [ 41 ]. This suggests that CPR5-PNET1 may have a dual function between cell cycle and immune pathways in the nuclear pore.…”
Section: Discussionmentioning
confidence: 99%
“…Only one comprehensive analysis has been found that focuses on EMG-driven control in lower limb prostheses [ 41 ]. Whereas various reviews have been published on MLLPs, most of these focus on mechanics and control, and either do not discuss EMG-driven control [ 50 , 52 , 69 ], or dedicate a short section to it [ 42 , 84 , 124 , 131 ].…”
Section: Introductionmentioning
confidence: 99%